Pesantren dan Kewirausahaan (Studi terhadap Pesantren Darul Khair Masing Kabupaten Banggai) - Israfil Israfil (Universitas Muhammadiyah Makassar, 2017)
Abstract. Like a pesantren in a rural area with minimal facilities and infrastructure, away from the hustle and bustle of the city, and not burdening the cost of education to santrinya, of course, required a leader figure to initiate entrepreneurship to develop the empowerment of boarding. This study aims to determine the empowerment of pesantren through entrepreneurship developed. This research is qualitative descriptive research with method of data settlement through interview, observation involve, and documentation study. The results show the form of entrepreneurship developed in Pesantren Darul Khair Each in the form of carpentry business, cattle farming, plantation, rice fields and pesantren co-operatives. All business assets and business results to the foundation periodically every month. Allotment is used for the financial costs of boarding schools such as the cost of building and dormitory, electricity payment, air taps, telephone every month, the welfare of its managers such as teacher salaries, the cost of education of three teachers in Java, assisting extracurricular activities of santri and daily consumption of santri hostel.Keywords: economy, entrepreneurship, pesantren.